Enhancing Arabic Speaking Skills through Vocabulary (Mufrodat) Mastery: The Effectiveness of the Durusul Lughah Textbook among MTs Students in an Islamic Boarding School - Madah Rahmatan; Muhammad Kurniawan AR; Muhammad Ridho Pratama; Dewi Sartika; Malikul Khandias (Lingu, 2026)
Purpose – This study investigates the effectiveness of systematic vocabulary (mufrodat) mastery through the Durusul Lughah textbook in improving the Arabic speaking skills (maharah kalam) of seventh-grade students at Pondok Pesantren Al-Ayyubi Jambi. Design/methods/approach – The research employed a quantitative approach using a quasi-experimental design with a one-group pre-test and post-test model to measure students’ speaking performance before and after the instructional intervention. The participants consisted of 24 students selected through a total sampling technique, and data were collected through an objective test designed to assess vocabulary mastery supporting speaking competence. Findings – Descriptive statistical analysis revealed that the mean score increased significantly from 67.92 in the pre-test to 96.67 in the post-test, accompanied by a reduction in the standard deviation from 14.28 to 7.45, indicating both improvement in overall performance and greater consistency among students. Furthermore, all students moved into the high-ability category after the intervention, demonstrating the strong instructional impact of structured vocabulary learning using Durusul Lughah. These findings highlight that contextualized vocabulary instruction can effectively facilitate the transformation of receptive language knowledge into productive speaking competence. However, the study is limited by its single-group design, small sample size, and focus on a single educational institution, which may restrict the generalizability of the findings. Research Implications – Pedagogically, the results suggest that Arabic language instruction at the MTs level should prioritize systematic vocabulary mastery as a central component of speaking development. Future studies are therefore recommended to employ experimental designs with control groups, larger samples, and longitudinal approaches to further examine the long-term impact of vocabulary-based Arabic learning on students’ communicative competence.